2000
DOI: 10.1016/s1083-8791(00)70066-8
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood stem cell transplantation in multiple sclerosis with busulfan and cyclophosphamide conditioning: Report of toxicity and immunological monitoring

Abstract: Multiple sclerosis (MS) is an immune-mediated disease that may be amenable to high-dose immunosuppression with peripheral blood stem cell transplantation (SCT) in selected patients. Five MS patients (all women, ages 39-47 years) received granulocyte colony-stimulating factor (G-CSF) for stem cell mobilization, CD34 cell selection for T-cell depletion, a preparatory regimen of busulfan (1 mg/kg x 16 doses) and cyclophosphamide (120 mg/kg), and antithymocyte globulin (10 mg/kg x 3 doses) at the time of stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 47 publications
6
95
0
1
Order By: Relevance
“…Treatment-related mortality ranged from 4 [30] to 20 % [42] during the first decade of HSCT for MS. This may in part reflect the selection of patients with advanced disability, as well as the use of high-intensity conditioning regimens.…”
Section: Lesson 2: Increasing Experience Using Hsct For Patients Withmentioning
confidence: 99%
“…Treatment-related mortality ranged from 4 [30] to 20 % [42] during the first decade of HSCT for MS. This may in part reflect the selection of patients with advanced disability, as well as the use of high-intensity conditioning regimens.…”
Section: Lesson 2: Increasing Experience Using Hsct For Patients Withmentioning
confidence: 99%
“…By contrast, non-myeloablative regimens selectively target the immune compartment for ablation without irreversible erasure of the BM's ability to regenerate hematopoiesis. Intense myeloablative regimens used to treat MS, such as BU/ CY 27 and CY/TBI/antilymphocyte globulin (CY/TBI/ ATG), 28 showed significant treatment-related mortality. An intermediate-intensity conditioning regimen, BEAM (BCNU, cytosine arabinoside, melphalan and etoposide) is better tolerated and has a lower morbidity and mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…34 The mortality rate of HSCT for MS in studies with relatively large samples is described in Table 1. [25][26][27][28][29][30][35][36][37][38][39][40][41][42][43][44][45] Although these studies use myeloablative conditioning regimens of varying intensity, non-myeloablative regimens have been advocated for autologous HSCT of autoimmune diseases. 46 Recently, one of these latter studies was published using CY/rATG and it reported no deaths among 21 patients with relapsing-remitting MS. 31 There is a controversy regarding the analysis of the immune system modifications as increases in naive CD4 þ T cells over memory cells 20 and the fact that more intensive regimens seem to present better results than less intensive regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, several regimens included the use of total body irradiation (TBI) [10] and busulfan [11,14,15]. These regimens were associated with high morbidity and mortality [14,16].…”
Section: History Of Ahct In Msmentioning
confidence: 99%
“…Initially, several regimens included the use of total body irradiation (TBI) [10] and busulfan [11,14,15]. These regimens were associated with high morbidity and mortality [14,16]. TBI was postulated to accelerate progression of disability in patients with secondary and primary progressive forms of MS as a result of the radiation-induced axonal damage [17].…”
Section: History Of Ahct In Msmentioning
confidence: 99%